Analysis of Customer Relationship Management and Social Media on Marketing Performance Mediated Digital Marketing at Gramedia Medan - Mhd. Rizky Perdana Putra; Nurafrina Siregar; Mesra B (International Journal of Management, Economic and Accounting, 2025)
This research aims to test and analyze the influence of customer relationship management, social media on marketing performance mediated by digital marketing at Gramedia Medan. Good customer relationship management and effective use of social media have an important role in improving marketing performance. Apart from that, integrated digital marketing is a key factor in mediating the influence of these factors on marketing performance. The research method used is a quantitative approach, with sampling based on the Slovin formula to determine the number of respondents who are representative of the population. The population of this study was Gramedia visitors in Medan City, which from the average visitor report per week, 442 people. With a margin of error of 5%, a sample of 210 respondents were selected randomly. Data was collected through a structured questionnaire. Data analysis was carried out using the Structural Equation Modeling (SEM) technique to test the relationship between the variables studied. The research results show that Customer Relationship Management has a positive and significant effect on marketing performance at Gramedia Medan, Social Media has a positive and significant effect on marketing performance; Digital Marketing has a positive and significant effect on marketing performance; Customer Relationship Management has a positive and significant effect on Digital Marketing, Social Media has a positive and significant effect on Digital Marketing. The results of this research also provide recommendations for Gramedia management to improve customer relationship management and the use of social media to improve marketing performance through digital marketing in strengthening Gramedia services in Medan.